1999
DOI: 10.1046/j.1365-2567.1999.00893.x
|View full text |Cite
|
Sign up to set email alerts
|

Up‐modulation of interferon‐γ mediates the enhancement of spontanous cytotoxicity in prolactin‐activated natural killer cells

Abstract: SUMMARYProlactin (PRL) has been shown to participate in lymphocyte activation. In particular, the constitutive natural killer (NK) and the lymphokine-activated killer (LAK) cytotoxicity of CD56 + CD16 + cells is increased by its physiological to supraphysiological concentrations. As PRL has been shown to up-regulate the production of interferon-c (IFN-c) by peripheral blood mononuclear cells, we studied its effect on IFN-c production by NK cells as a possible mechanism of autocrine activation of cytotoxicity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 38 publications
2
24
0
3
Order By: Relevance
“…NK cells also express IFN-␥ mRNA and release IFN-␥ in the presence of pituitary or recombinant PRL. 54 Cessario et al 55 reported enhanced yields of IFN-␥ in PRL-treated human peripheral blood mononuclear cells and correction of a defect in IFN-␥ production and altered lymphocyte proliferation in bromocriptine-treated mice with PRL supplementation. 1,10 Delayed or abrogated rejection of tumor in allogenic mice with anti-IFN-␥ antibody 56 and suppression of PRL-mediated augmentation of NK activity in the presence of anti-IFN-␥ MAb 54 further suggested that PRL may regulate antitumor immune responses through IFN-␥.…”
Section: Discussionmentioning
confidence: 99%
“…NK cells also express IFN-␥ mRNA and release IFN-␥ in the presence of pituitary or recombinant PRL. 54 Cessario et al 55 reported enhanced yields of IFN-␥ in PRL-treated human peripheral blood mononuclear cells and correction of a defect in IFN-␥ production and altered lymphocyte proliferation in bromocriptine-treated mice with PRL supplementation. 1,10 Delayed or abrogated rejection of tumor in allogenic mice with anti-IFN-␥ antibody 56 and suppression of PRL-mediated augmentation of NK activity in the presence of anti-IFN-␥ MAb 54 further suggested that PRL may regulate antitumor immune responses through IFN-␥.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that PRL exhibited a dose-dependent enhancement upon both IgM and IgG secretion treated with anti-IgM and IL-2 or anti-IgM alone in vitro [15,16], indicating that PRL may affect peripheral B-cell function. PRL also increased the proliferating response and cytotoxicity of human, murine or rat NK cells to sensitive or insensitive tumor independently or synergistically with IL-2 in vitro [17][18][19][20]. We previously reported that PRL improved the hematopoiesis and lymphocyte development in syngeneic bone marrow transplantation [21][22][23][24], and exerted anti-tumor effects on tumor-bearing mice in vivo [25].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, PRL stimulates inducible NO synthase production, Ig release, and cytokine expression in human leukocytes (7)(8)(9)(10). Furthermore, PRL has anti-apoptotic properties that have been demonstrated in the Nb2 rat lymphoma (11) and in dexamethasone-treated thymocytes (12).…”
mentioning
confidence: 97%